Syncronization of Certified Intenship Program in the Implementation of Merdeka Belajar and Kurikulum Merdeka - Eko Supraptono; Ulfa Medaty Arief; Henry Ananta; Muhammad Harlanu; Putri Khoirin Nashiro (Universitas Negeri Semarang, 2022)
The implementation of the Internship program in the context of